“Estrategias comunicacionales internas del GADM Riobamba y su aporte a la construcción de la imagen corporativa. periodo enero-junio 2019”. - Angie Justine, Aguirre Izurieta (2020)
The internal communication strategies of the GADM Riobamba and its contribution to the construction of the corporate image. Period January-June 2019. It is a research work focused on internal strategies and about the management and the effectiveness they have when it comes to contributing to the construction of the corporate image of the municipality. Besides, it allows knowing the citizen’s perception of the institutional image of the GADM Riobamba. In general, this research has tried to determine and evaluate the strategies applied by the GAM Riobamba. Therefore, the study is based on the theoretical foundation, theories, and basic fundaments and necessary foundations to support the research. The methodology used to obtain the information that is part of the research is bibliographic and field documentary. The quantitative and qualitative approach complements it. Data collection instruments were also applied, such as surveys aimed at employees, workers, managers, and contract staff working in the different Decentralized Autonomous Government departments of the Riobamba canton. Moreover, surveys directed at the PEA of the Riobamba Canton and interviews directed at experts in the subject. The results have allowed us to obtain relevant information about the topic of this research. Finally, based on the objectives set out in the investigation, the conclusions and recommendations it is proposed the development of a manual for the construction of internal communication strategies that allow to improve and enhance corporate image of the GADM Riobamba.